Preparación de formulaciones tópicas a base de Ipomoea batatas y su evaluación microbiológica de patógenos - Salinas Maqui, Leslie Nicole Solansh (2023)
This research aimed to prepare topical formulations based on Ipomoea batatas and perform their microbiological evaluation of pathogens. The evaluation was carried out following the procedure that consisted of preparing 03 topical formulations based on hydroalcoholic extracts of stems, leaves and peels of Ipomoea batatas in the form of gels; including in the preparation basic components such as 70° ethyl alcohol, carbopol, glycerin, propylene glycol, triethanolamine and purified water c.s.p. Then the topical formulations were subjected to microbiological tests to determine the presence or absence of pathogenic microorganisms: Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans, according to the regulations of the United States Pharmacopeia (USP 44 - NF 39). It is concluded that the topical gel formulations of Ipomoea batatas leaves and peel gel meet the USP specifications, as they do not present growth of pathogenic microorganisms, while the gel from the stem of Ipomoea batatas does not meet the established microbiological quality specifications, due to the growth of Staphylococcus aureus